Asceticism as a Driving Factor of Marriage: Study of Marriage Syar'i Hijab Student - Fauziyah, Umi Nur; Suhartini, Elly (Laboratorium Sosiologi FISIP Universitas Jember, 2019)
Asceticism is the desire to be blessed to be closer to the creator. Asceticism can be a motivation for Marriage at a young age. Marriage is often interpreted as something very crucial for humans. This study aims to determine the reasons for marriages conducted by Shari hooded female students by using Peter L. Berger and Thomas Luckman's social construction theory. This study uses qualitative research methods with a constructivist approach. The results showed that asceticism was the main factor causing marriages among Shari veiled female students. Other factors are obedience to parents, obedience to husband, happiness, norms, and rizq obtained, involvement in religious activities. The decision to get married chosen by students has a positive and negative impact on life lived both in the academic field and in everyday life. Keywords: asceticism, syari students, marriage. Referensi: Carl W Ernist, The Shambala Guide to Sufism. Shambala Publication Inc., Boston, 1997. Hadiwijono, Harun, Seri Sejarah Filsafat Barat I. Kanisius,Yogyakarta, 1980 IAIN Syarif Hidyatullah, ”Zuhud